Zigler's conceptualization of diversity: Implications for the early childhood development workforce. (May 2021) - García Coll, Cynthia; Ferrer, Kia L.
Abstract: The United States is entering a pivotal period in history, led by extraordinary shifts in the demographic makeup of children who are in need of medical, educational, and developmental services. For the first time in this country's history, the majority of children are being born to non-white populations. Simultaneously, racism (personal, institutional, and systemic) is now being recognized as a powerful social determinant of children's mental and physical health by the time they enter kindergarten. It is crucial to evaluate how early childhood development (ECD) settings are prepared to authentically engage racially diverse children. In this paper, we critically analyze the narratives of the architect of Head Start, Dr. Edward Zigler, and investigate his evolving contributions to early childhood programming. We propose that Zigler's conceptualization of culture and its impact on children's development, although advanced for his time, had historical limitations that have perpetuated the personal, institutional, and systemic racism that children of color experience in early childhood settings. This paper concludes with suggestions to include topics covering implicit bias, white privilege, and the impact of slavery, colonization, and oppression as core principles in professional training. Only then will we be able to eliminate racism across early childhood settings in the United States.